Environmental effects on degradation behavior in YbGdSi ternary system at elevated temperatures. Issue 13 (1st July 2021) - Arai, Yutaro; Morigayama, Hiroki; Aoki, Takuya; Inoue, Ryo
Abstract: The degradation behavior of Yb- and Gd-based ternary silicides (YbGdSi) was evaluated in Ar, 50 vol%air-H2 O (air-H2 O), and 100 vol%H2 O (steam) environment and compared with the results obtained in a previous study conducted in air environment. Heat exposure at 1200 °C for 1, 2, 4, and 8 h was carried out in addition to thermogravimetric analysis up to 1200 °C. The results of these studies demonstrated that YbGdSi formed complex oxides in the (Yb- and/or Gd)-Si-O system and Yb2 O3 was commonly formed for each environment. In addition, the resultant weight gain for YbGdSi in air, air-H2 O and steam decreases by 2–5% in comparison with it for Yb3 Si5 . These results clearly indicate that the addition of Gd was effective in preventing the degradation of Yb-silicides.